SQUARE ROOT AND 3RD ROOT FUNCTIONAL EQUATIONS IN C^*-ALGEBRAS: - Park, C. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2011)
In this paper, we introduce a square root functional equation anda 3rd root functional equation. Using fixed point methods, we prove the Hyers-Ulam stability of the square root functional equation and of the 3rd root functional equation in Coalgebras.